Romero, Raúl. All musics. Sound and cultural diversity in Peru. Ethnographic Studies Series. Volume 8 Lima, PUCP Institute of Ethnomusicology 2017. 296 pp - Nugent, Guillermo (2018)
The book All musics. Sound and cultural diversity in Peru, can be described as a foundational work. It is made up of ten essays that develop multiple musical scenes; the Andean predominates, but Creole, Afro-Peruvian, classical music and a field of musical fusion are also included. This work by Romero lays the foundation for the creation of a new field of study: ethnomusicology in Peru.